Consequences of rising humidity level on circulatory responses during prolonged intense exercise - Ahmad Munir, Che Muhamed (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe